Expectations of an Online-Self-Management Program for Rheumatoid Arthritis. (July 2022) - Chen, Su-Hui; Yu, Kuang-Hui; Lee, Yi-Hui; Shao, Jung-Hua
This qualitative descriptive study aimed to explore expectations of patients and healthcare experts for an online self-management program for rheumatoid arthritis. Participants were recruited from rheumatology clinics, medical centers, and universities in Taiwan. Individual face-to-face, semi-structured interviews were conducted with patients ( n  = 16) and healthcare experts ( n  = 7). Content analysis of the interview data resulted in five subthemes for expectations of an online self-management program: information about how the disease trajectory would impact future health status, availability of opportunities for self-monitoring, opportunities to interact with fellow patients and healthcare providers, simplicity and ease-of-use of the program, and methods to facilitate patient-motivation. These subthemes formulated two overarching themes: content and format. An online self-management program for patients with rheumatoid arthritis should provide evidence-based information about disease variables and behaviors aligned with the specific needs of the individual and adopt strategies that encourage and increase motivation and confidence.